Applicability of the diffusion of innovation theory to accelerate model‐based systems engineering adoption. Issue 6 (9th September 2022) - Call, Daniel R.; Herber, Daniel R.
Abstract: Systems engineering (SE) is an interdisciplinary domain that can benefit from incorporating contributions from fields not typically associated with technical disciplines, including integrating relevant research from social sciences. The study of innovation has produced the diffusion of innovation theory, which identifies variables that affect the adoption rate of innovations. Of these variables, the perceived attributes of the innovation have been shown to have the most significant impact on the adoption rate of innovations. Shaping the innovation attributes of relative advantage, compatibility, complexity, trialability, and observability and how they are perceived can accelerate its adoption rate. This theory has the potential to accelerate the adoption rate of SE innovations. Model‐based systems engineering (MBSE) is an SE innovation that, despite its benefits, has not been adopted generally. An evaluation of the attributes of MBSE as defined by the diffusion of innovation theory can aid in understanding its slow diffusion and inform methods to accelerate its adoption. Since there is some evidence to suggest that this theory is applicable to SE and MBSE, additional research should be conducted to determine the best way to utilize its principles.